Delineating caregiver distress and health condition of dementia sufferers during lockdown due to COVID-19 pandemic - Ruchira Mukherjee; Bidisha Bhattacharyya; Adreesh Mukherjee; Gautam Das; Sujata Das; Atanu Biswas (Annals of Medical Science and Research)
Objectives: The COVID-19 pandemic led several countries to go under strict lockdown, including India. This was mainly done to limit the spread of the virus by ensuring social distancing and following the other COVID-19 protocols. Managing and caregiving of chronic disorders like dementia became challenging. The aim of the study was to delineate the health condition of demented patients and distress of their caregivers during the lockdown caused by the COVID-19 pandemic. Methods: A telephonic survey was conducted to collect the data of 57 participants who had attended the cognitive clinic of our institute for a follow-up within 1 year preceding the lockdown. Demographic details of the patient and caregivers were noted followed by the questions related to the patients' health and their caregivers' distress during the lockdown. The questionnaire had two parts: (a) Patient Health Condition (PHC)'(b) Caregiver Distress-which consisted of preexisting caregiver distress before the lockdown and increase during the lockdown. Results: During the lockdown, 89.5% of caregivers reported increase in caregiver distress and 61.4% reported deterioration in PHC, including worsening of memory and behavioral symptoms. Caregivers reported increased feelings of sadness and hopelessness (65%), physical exhaustion (60%), investment of energy (67%), and anxiety of getting sick with nowhere to turn for support (51%). The increase in caregivers' distress during the lockdown was higher with a decline in patients' health condition and in female caregivers and severe stages of dementia. Conclusion: The lockdown situation was detrimental to both the patients' health condition and caregiver distress in dementia.